Functional Scattered DataG1 Interpolation With Sum Of Squares Of Principal Curvatures. - Saaban, A.; Majid, Ahmad Abd; Piah, Abd. Rahni Mt.; Chang, L. H. T. (2005)
Scattered Data interpolation deals with fitting of a smooth surface to set of non-uniformly distributed data points which extends to all positions in a domain.